PENGARUH SEKTOR-SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DAN LAJU PERTUMBUHAN EKONOMI KABUPATEN MANGGARAI BARAT - Aneldus, Stefen Yustinus; Urmila Dewi, Made Heny (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 7 (2020): VOL 9 NO 7, JULI 2020 (1431-1630), 2020)
ABSTRACT West Manggarai Regency tourism sector is one sector that has the potential to be developed to increase local revenue and West Manggarai Regency economic growth. West Manggarai Regency has increased its tourism sector more than the maritime sector while its cultural and natural tourism sector is not developed enough. This study aims to determine the effect of the number of tourist visits, length of stay of tourists, and hotel occupancy rates on local original income and economic growth in West Manggarai Regency. The data used in this study are secondary data obtained from related agencies. The data obtained is then processed by path analysis through SPSS assistance. The results of this study conclude that the number of tourist visits, length of stay of tourists, and hotel occupancy rates have a positive and significant effect on local income, while the number of tourist visits has a positive and significant effect on economic growth in West Manggarai Regency, length of stay of tourists and hotel occupancy rates have a positive effect and not significant to the economic growth of West Manggarai Regency. Regional original income has a positive and significant effect on economic growth in West Manggarai Regency. Keywords : Number of tourist visits, length of stay of tourists, hotel occupancy rates, local revenue, economic growth